Jalan Buntu atau Terobosan Memahami Penawaran Tender dalam Akuisisi di Indonesia dan Isu Pengendalian Perusahaan Ganda - Firmansyah, Bilal (UI Scholars Hub, 2024)
Corporate actions are commonly undertaken by companies to gain profits. An acquisition is one example of a corporate action that generates positive sentiment in the market, thereby attracting the attention of many companies. However, as a consequence of an acquisition, each company involved is required to make a mandatory tender offer for the remaining shares not acquired during the acquisition process. This mandatory tender offer is regulated by the Financial Services Authority Regulation No. 9/POJK.04/2018 (Regulation on the Takeover of Public Companies), which allows for certain exceptions in its implementation. The issue arises when the exception to the mandatory tender offer is applied to the shares of another controlling shareholder, which in this case initiates external control outside the acquiring company. The results of the study indicate that the exception to the mandatory tender offer for the shares of another controlling shareholder creates a dual control issue, which ultimately harms the interests of the acquiring company. Dual control undermines the essence of an acquisition since the transfer of control, which is supposed to happen, is confronted with another controller after the acquisition process is completed.